Observations on the flight activity of the Pine processionary moth Thaumetopoea pityocampa (Den. & Schiff.) in Greece, using synthetìc sex-pheromone and light traps (Insecta Lepidoptera Thaumetopoeidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The flight activitles of the pine processionary moth, Thaumetopoea pityocampa were observed using sex pheromone and light traps in the summer of 1990 in the Taigetos Mts. (Greece) at altitudes from 800 to 1450 m. Sex pheromones synthesized in ltaly and Spain were successfully used in the traps in Greece. A new model of pasteboard traps was astonishingly effective. Altitude was found to have a major impact on the timing and duration of adult emergence and larva! hatching. Above 1300 m, hatching began as early as June, most probably in order to utilize the period of favourable weather in summer and autumn for embryonic and post-embryonic development. The circadian rhythm of the moths involved activity late in the evening, slowing down toward midnight. Although a couple of gravid moths were caught in the light trap, females were not observed to be capable of flight.
Keywords: Thaumetopoea pityocampa; Greece; sex pheromone; pheromone traps; light traps